EFEKTIVITAS MELT BLOWN FILTER CARTRIDGE DAN SINAR UV-C TERHADAP PENURUNAN TOTAL COLIFORM PADA AIR PROSES PRODUKSI DI PT. X - Nursyifa Yuliani Putri; Elanda Fikri; Nany Djuhriah (Politeknik Kesehatan Kemenkes Bandung, 2021)
Water is a basic need for humans, water related to the results of the food processing industry must have the quality standards required for drinking water. PT. X is industry engaged in the production of bread. Production process water is sourced from artesian wells and through a physical treatment process. The results of microbiological examination of the total Coliform parameters not eligible 8.6 APM/100ml with a quality standard of 0 APM/100ml. Regulation the minister of Health RI 492 of 2010 Drinking Water Quality Requirements, therefore it is necessary to treat the production process water using a Melt Blown filter cartridge and UV-C light. The purpose of this study was to reduce the total Coliform and determine the effectiveness of the Melt Blown filter cartridge and UV-C light with variations of the Melt Blown filter cartridge 10” 1 micron, 3 micron, and 5 micron. This type of research is an experimental research with a pretest-posttest without control research design. The sample in this study was water from the chiller reservoir Building B. The average total Coliform after being treated using a Melt Blown filter was 1 micron 2.95 APM/100ml, 3 microns 3.61 APM/100ml, 5 microns was 7.31 APM/100ml with percentage reduction of 100%, 94.5% and 82.4%, respectively. The average total Coliform after being treated with ultraviolet-c light resulted in a decrease of 1 micron and UV-C 2.95 APM/100ml, 3 microns and UV-C 3.95 APM/100ml, 5 microns and UV-C 8.88 APM/100ml with a percentage reduction of 100%, 100%, 100%. Data analysis was performed using One Way Anova with p value 0.001. The effective variations are 1 micron and UV-C light.